Floral Genetics of African Nightshade (Solanum section Solanum) - Ojiewo, Christopher Ochieng; Murakami, Kenji; Masinde, Peter Wafula; Agong', Stephen G. (International Journal of Plant Developmental Biology, 2007)
Solanum section Solanum, centering on the species commonly known as African nightshade, and botanically known as the “Solanum nigrum complex” is composed of a large number of morphogenetically distinct taxa, with certain common features. Their wide tolerance of habitat types, early flowering and prolific fruit production are adaptive features for success in the wild, semi-wild or weedy forms. In most parts of Africa and south-east Asia, their consumption, demand and market value as leafy vegetables have been on the rapid and steady rise in recent years due to their high nutritional and health benefits. However, production of these vegetables has traditionally remained on kitchen-garden scales with very low leaf yields. Notably, competition between vegetative and reproductive functions accounts for this low yield. Accurate manipulation of the switch from vegetative to reproductive development or elimination of the latter would potentially delay, reduce or eliminate competition from excess fruit load. A thermosensitive abnormal floral organ mutant (T-5) with sepaloid, stamenless and indeterminate phases has been induced in the sub-taxon S. villosum. The mutant will form an important basis for understanding reproductive developmental steps, such as floral induction, meristem formation, and organ development in African nightshade. This review explores the established floral genetic models as a basis to elucidate the aspects of floral genetics of African nightshade, with special reference to the T-5 mutant. __________________________________________________________
Keywords: abnormal floral organ; floral architecture; restoration; Solanum nigrum; temperature-dependent